Mechanistic insights into phosphorus transformation mediated by Arthrobacter and Sordariomycetes under long-term high-volume swine manure application in a wheat-rice rotation system - Zhang, Chunlong; Zhang, Shuang; Tang, Xiaoyan; Zhang, Bin; Liu, Dejun; Yang, Zepeng; Huang, Rong; Wu, Yingjie; Tao, Qi; Luo, Youlin; Wang, Changquan; Li, Bing (Frontiers in Microbiology, 2025)
IntroductionUnderstanding the impacts of sustained high-input swine manure on soil phosphorus (P), along with identifying and functionally characterizing P-associated microorganisms, can provide a scientific foundation for effective management of soil P in relation to swine manure application. This study provides novel insights into the functional roles of P-associated microorganisms in mediating phosphorus dynamics under long-term excessive swine manure application.MethodsThe study investigated the prolonged impact of high-volume swine manure application on soil P fractions over an 8-year continuous, randomized field trial involving rotating wheat (wet conditions) and rice (flooded conditions) crops. And the soil treated with the prolonged high- volume swine manure application was selected to isolate and identify specific microorganisms, which were subsequently inoculated into soil previously treated with long-term NPK fertilizer (F) and swine manure application (M) for indoor cultivation and functional characterization verification.ResultsThe sustained high input of swine manure markedly enhanced soil P activity and microbial P content (P < 0.05), specifically extracting P-associated microorganisms, namely Arthrobacter sp. M4 bacteria and Sordariomycetes 2 MS-M4 fungi. Upon separate inoculation of these microorganisms into high-Carbon (C) and high-P soils (M soil, Olsen P > 70 mg kg–1, ROC > 150 mg kg–1), it was observed that both microorganisms effectively converted available P sources (Ca2-P, Ca8-P) into organic P reserves through biological immobilization. Conversely, under conditions of low C and low P (F soil, Olsen P < 10 mg kg–1, ROC < 75 mg kg–1), there was an enhancement in the decomposition and utilization of soil organic C which resulted in increased effective P content via the breakdown of organic phosphates—demonstrating a robust capacity for P transformation. Furthermore, when these phosphate-related microorganisms were introduced to long-term fertilized soils enriched with NPK fertilizer (F), they exhibited a significantly greater enhancement in soil P availability compared to those inoculated into soils subjected to prolonged high inputs of swine manure.DiscussionThe P-related microorganisms Arthrobacter sp. M4 and Sordariomycetes 2 MS-M4 extracted from soils with high P availability were confirmed to have the key functions of enhancing the fixation of inorganic P into organic P (high-C and high-P condition) or promoting the activation of organic P into rapidly available P (low C and low P level). Which may plays an important role in the management of agricultural P nutrients.